2021
DOI: 10.29121/granthaalayah.v8.i12.2020.2676
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity and Phytochemical Screening of Mangifera Indica Ethanol and Aqueous Leaves Extract Against Pseudomonas Aeruginosa and Staphylococcus Aureus

Abstract: The aim of this research is to investigate the antibacterial activity and identify the phytochemical constituents of Mangifera indica leafs on Pseudomonas aeruginosa and Staphylococcus aureus using disc diffusion method. The sample was collected fresh from the premises of Bioresources Development Center (BIODEC), Katsina, Katsina State and was dried and pounded into powder. The powdered leaves were extracted using ethanol and aqueous solvents. Various concentrations ranging from 500mg to 62.5mg were prepared. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…17 In this study, Spondias mombin stem bark, leaves and charcoal ethanol and aqueous extracts all exhibited antimicrobial activities at varying concentrations (with the exception of 62.5mg/ml of ethanol and aqueous extracts of the stem bark and leaves extracts) in zone of inhibition assay. This result from zone of inhibition was similar to the research carried out by Garga, Garasin 18 and Mada, Garba 19 who reported that the higher the concentrations of both extracts, the higher the antibacterial activities against test organism.…”
Section: Discussionsupporting
confidence: 89%
“…17 In this study, Spondias mombin stem bark, leaves and charcoal ethanol and aqueous extracts all exhibited antimicrobial activities at varying concentrations (with the exception of 62.5mg/ml of ethanol and aqueous extracts of the stem bark and leaves extracts) in zone of inhibition assay. This result from zone of inhibition was similar to the research carried out by Garga, Garasin 18 and Mada, Garba 19 who reported that the higher the concentrations of both extracts, the higher the antibacterial activities against test organism.…”
Section: Discussionsupporting
confidence: 89%
“…Punica granatum plant extract contains terpenoids, steroids, phenols, alkaloids, flavonoids, glycosides, carbohydrates, and protein in different solvent extracts; the same findings were reported by 20 . In Moringa oleifera extract also contains alkaloids, flavonoids, tannins, glycosides, carbohydrates, and phenol were there in different solvent extraction, our results were concurrence with 6 . Alkaloids, flavonoids, steroids, terpenoids, tannins, phenol and protein are there in different solvent extraction of Momordica charantia; similar findings were reported by 7 .…”
Section: Resultssupporting
confidence: 83%
“…family and is used to treat various ailments such as diarrhea, common cold, toothache, and oedema 6 . Momordica charantia belong to the Cucurbitaceae family and are used medicinally to treat many diseases like piles, leprosy, jaundice, diabetes, and snake bite 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In case of M. indica leaves, both the cold and hot water extracts showed sensitive to Staphylococcus aureus, Bacillus sp., P. aeruginosa, Salmonella sp, and E. coli but resistant to Klebsiella sp. and produced a comparatively lesser zone of inhibition than S. cumini leave extracts Garga et al 2020. also reported that water extract of M.indica leaves was sensitive to S.…”
mentioning
confidence: 92%